Escaping the Trough: Towards Real-World Impact of Tabletop Research. Issue 2 (1st February 2017) - Bruun, Anders; Jensen, Kenneth Eberhardt; Kristensen, Dianna Hjorth; Kjeldskov, Jesper
ABSTRACT: In the past decade, there has been increasing interest in studying tabletop technologies in HCI. Using the Gartners Hype Cycle as an analytical framework, this article presents developments in tabletop research within the last decade. The objective is to determine the level of maturity of tabletop technologies with respect to the research foci and the extent to which tabletops have shown their worth in real world settings. We identify less studied topics in the current body of literature with the primary aim of evoking further discussions of the current and future research challenges. We analyzed 542 research publications and categorized these according to eight types of research foci. Findings show that only 3% of all studies are conducted in natural settings, i.e. there is a clear tendency to emphasize laboratory evaluations of tabletop technology. Also, very few studies demonstrate relative benefits of tabletops over other technologies in collaborative settings (1%). We argue for a need to increase emphasis on understanding real-world use and impact rather than developing new tabletop technologies.